PENGARUH AUTOGENIC TRAINING TERHADAP PENERIMAAN DIRI KELUARGA MERAWAT PASIEN SKIZOFRENIA - Isnawati, Iin Aini; Yunita, Rizka (Journal of Nursing Care and Biomoleculer, 2019)
Schizophrenia is a brain disease and belongs to a type of serious mental disorder that causes individuals to experience changes in emotions, perceptions, and thought patterns. This condition often triggers maniac behavior and acts of violence. This situation makes the family refuse to accept the client's situation because they feel embarrassed, ostracized, ridiculed, insulted, avoided until they are expelled by society. The financial amount for medical expenses is also a family stressor. One solution to overcome this problem is through autogenic training. The purpose of this study was to analyze the effect of autogenic training on the self-acceptance of families caring for schizophrenic patients. This research method uses quasy experimental with one group pre-post test design. The population and sample of this study were 36 families who were treating schizophrenic patients in the Maron Health Center Working Area, Probolinggo District. The sampling technique uses total sampling. The results of this study indicate a value of ? of 0,000 so that there is an autogenic training effect on the self-acceptance of families caring for schizophrenic patients.